Assessing the Relationship between Body Image Satisfaction and Physical Activity in Italian Adolescents: A Cross-Sectional Investigation - Sabrina Masotti; Tommaso Piva; Valentina Zerbini; Andrea Raisi; Erica Menegatti; Anselmo Pagani; Costanza Bigoni; Elena Ballarin; Federica De Luca; Luciana Zaccagni; Natascia Rinaldo; Stefania Toselli; et al. (MDPI AG, 2024)
Background: Body image perception can significantly influence various aspects of adolescent lives. The study analyzed the relationship between body image satisfaction and sports participation in adolescents, examining various factors that contribute to body image concerns and their implications for sports engagement. Methods: A total of 237 schoolchildren were recruited from lower secondary Italian schools. Anthropometric characteristics were measured directly. Assessment of body image perception was performed using Body Silhouette Charts for preadolescent children. The Italian version of the International Physical Activity Questionnaire for Adolescents questionnaire was administered to assess physical activity (PA) levels at school and during leisure time in the last 7 days. Analysis of variance was used to test differences in PA levels, while multiple regression models were carried out to assess possible predictors of body dissatisfaction. Results: In total, 42.6% of children were not satisfied with their figure and 23.2% were very dissatisfied; among them, the vast majority would have liked to be thinner. The dissatisfaction and satisfaction were similar in boys and girls. The frequency of satisfaction with one's body image was higher in children who practiced extracurricular sports compared to those who did not. The percentage of dissatisfaction with one's body image was similar in the two groups, but the frequency of children being very dissatisfied was double in the group that does not practice extracurricular sport (31.2% vs. 17.7%). Body dissatisfaction increases with increasing body mass index in both genders but decreases in children involved in extracurricular sports. Conclusions: Encouraging teenagers to engage in regular physical activity should be a key component of therapies supporting positive body image. This study found a relationship between extracurricular sports and body image satisfaction, suggesting that physical activity protects teenagers' body image satisfaction.